2019
DOI: 10.1002/cncr.32557
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer mortality and metastasis under different biopsy frequencies in North American active surveillance cohorts

Abstract: BACKGROUND: Active surveillance (AS) is an accepted means of managing low-risk prostate cancer. Because of the rarity of downstream events, data from existing AS cohorts cannot yet address how differences in surveillance intensity affect metastasis and mortality. This study projected the comparative benefits of different AS schedules in men diagnosed with prostate cancer who had Gleason score (GS) ≤6 disease and risk profiles similar to those in North American AS cohorts. METHODS: Times of GS upgrading were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…In addition, data from the pre-PSA era suggest that men not followed according to a strict protocol still have excellent PC survival [13] , [14] . Interestingly, our results are also well in agreement with a recent study in which a simulation model was developed to study the impact of biopsy frequencies on mortality and development of metastasis in men on AS [15] . The authors concluded that a less frequent biopsy schedule might be the preferable option.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, data from the pre-PSA era suggest that men not followed according to a strict protocol still have excellent PC survival [13] , [14] . Interestingly, our results are also well in agreement with a recent study in which a simulation model was developed to study the impact of biopsy frequencies on mortality and development of metastasis in men on AS [15] . The authors concluded that a less frequent biopsy schedule might be the preferable option.…”
Section: Discussionsupporting
confidence: 91%
“…Though some prostate cancer metastasis-related markers, such as serum miR-141 and exosomesderived miR-141-3p has been found [31,32], it is far from clinical application. Our finding that ephrin-A5 is disassociated from EphA3 and released outside the cell by ADAM10 suggests that ephrin-A5 may have certain diagnostic value in prostate cancer metastasis [33]. The similar ephrin-A5 content in serum of the patients with prostate cancer and BPH indicates that serum ephrin-A5 cannot be used as a marker of common prostate malignancy.…”
Section: Discussionmentioning
confidence: 89%
“…Given the prolonged natural history of prostate cancer, patients omitting PPSBx are unlikely to experience worse oncologic outcomes from the delay in upgrading by waiting for a change in clinical status, which would then have prompted a FCSBx. 25 Our study has several notable limitations. First, this a retrospective registry study of patients undergoing surveillance biopsies.…”
Section: Secondary Objectivesmentioning
confidence: 91%